Hyperuricemia as a Predictor of in-hospital Mortality in Acute Exacerbation of COPD: Insights from a Tertiary Care Hospital in Karachi - Sharif Ahmed Khan; Nausheen Ahmed (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To identify the correlation of hyperuricemia with in-hospital mortality in patients who report to a tertiary care hospital in Karachi with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). METHODOLOGY: This cross-sectional study was conducted from May to October 2024 at Jinnah Postgraduate Medical Centre (Ward 12, Chest Medicine Centre), Karachi, Pakistan. A total of 150 patients with AECOPD were included via non-probability consecutive sampling. Inclusion criteria comprised: age 40 years, confirmed COPD diagnosis via spirometry with reversibility (post-bronchodilator FEV1/FVC <0.70), and hospitalization for AECOPD (Anthonisen's criteria). Exclusion criteria included chronic kidney disease, gout, coexisting pulmonary diseases, uncontrolled comorbidities affecting uric acid levels, and pregnancy. Data on demographics, serum uric acid levels, and outcomes were collected. Statistical analysis was performed using SPSS version 26, employing Chi-square tests and one-way ANOVA to assess associations between hyperuricemia, age, COPD duration, and mortality. RESULTS: The cohort consisted of 71% males and 29% females, with 79% reporting a history of smoking. Hyperuricemia (>7 mg/dL) was significantly associated with in-hospital mortality (p = 0.001). A linear correlation was observed between age and uric acid levels (p = 0.014), but no association was found with COPD duration (p = 0.902). The mortality rate was 70%, higher than global averages, likely due to delayed presentations and limited ICU resources. CONCLUSION: Hyperuricemia was identified as a predictor of in-hospital mortality among patients with AECOPD. Early intervention and monitoring of elevated uric acid levels can improve clinical outcomes in this high-risk patient population.